Microeconomic Impact of Remittances at the Household Level in a Remittance Receiving Country, Bangladesh - Hossain, Md. Shahadat; Lee, Chin; Said, Rusmawati; Ishak, Suryati (Maya Global Education Society, 2020)
Purpose of the study: This paper aims to investigate the microeconomic impact of remittances at the household level in Bangladesh, which is one of the top remittance receiver’s countries in the world. The microeconomic factors, which have been include in this research, are per Capital consumption, per Capital food expenditure, poverty rate, health expenditure, education expenditure, and calorie intake. Methodology: The propensity Score Matching (PSM) technique has been applied to present the issue of self-selection associated with the migration decision and the scope of the receiving remittances. Based on the survey results of Household Income and Expenditure Survey (HIES) 2016 conducted in Bangladesh, this study includes the Microeconomic impact of remittances on the household level in Bangladesh including some variables such as the size of household, food calorie, expenditure on health and education, etc. Main Findings: Results show that the remittances have a significant microeconomic impact at the household level in Bangladesh. However, some of the findings are consistent with previous studies, while some others are not. Implications of the study have been discussed along with the concluding remarks. Applications of this study: The study can be useful for the government and house decision-makers to utilize the remittances sent by expatriates at the household level. Novelty/Originality of this study: There are no recent studies on the microeconomic impact of remittances at the household level in Bangladesh using the most recent survey, i.e. Household Income and Expenditure Survey (HIES) 2016. Previous studies were conducted based on Household Income and Expenditure Survey (HIES) 2010. Hence, this study contributes to the body of knowledge with recent variations on the microeconomic impact of remittances at the household level in a remittance-receiving country.